Scientific potential of the regions of the Republic of Belarus - O. N. Sikorskaya; M. A. Bovkunovich; O. N. Chikun (Библиосфера)
This article provides an overview of the scientific productivity of the regions of the Republic of Belarus according to the data of the scientometric systems Scopus and Web of Science. The aim of the work is to present the results of bibliometric analysis of research activities in separate regions of the country. The following indicators are calculated: the number of organizations and publications, citations, average citations per article, highly cited publications. The performed analysis is relevant, since the topic of the regional distribution of publication activity in the Republic of Belarus has not been covered yet in the professional press. The analysis showed that the scientific productivity of the regions in Belarus is at a low level, even with the observed increase in publication activity in recent years. The results obtained can be used as initial data by specialists in their further research, heads of scientific organizations for making managerial decisions in the field of scientific policy, determining the most promising areas of research, etc. It is concluded that in order to improve the results of research activities of the territorial-administrative regions in the Republic of Belarus, it is necessary to actively develop national and international scientific cooperation.